The use of nanomaterials in concrete: A review. (2022) - Goel, Gaurav; Sachdeva, Payal; Chaudhary, Akshay Kumar; Singh, Yadvendra
Abstract: After water, the most often utilised construction material is concrete. However, cement is a very brittle material with low ductility, low tensile strength, early formation, and micro-crack propagation due to shrinkage at young ages. Considering the previous two decades, the output of concrete has been greatly increased by using various supplementary cementitious materials (SCMs) and nanoparticles (such as SiO2, TiO2, Fe2 O3, Cr2 O3 and Al2 O3 ). Because of their small fragment size and increased surface area, nanomaterials have a high potential for improving concrete properties (such as compressive strength, split tensile strength and flexural strength, water permeability, abrasion resistance, and pore structure). The inclusion of nanoparticles in concrete and its consequences have been reviewed in this work. To make it easier to compare the effects of oxide nanoparticles on concrete, graphical representations of all of these parameters have been facilitated.